Role of Ayurveda in Stress and Related Disorders (International Journal of Ayurveda and Pharma Research, 2021)
Today is the world of competition and everybody is running day and night to achieve the best in their terms. The mankind is set into a new dimension of time where ceaseless activity throughout is making everybody restless. Overall result is the never ending physical and mental stress coming out in the form of variety of health disorders which can be called as stress related disorders like hypertension, coronary artery disease, arthritis, ulcerative colitis, irritable bowel syndrome, diabetes mellitus, thyrotoxicosis and behavioral disorders like anxiety and depression. Ayurveda mentions the stress as Sahas and its impacts on the body as aggravation of Vata Dosha and Ojokshaya leading to lowered immunity and resulting number of diseases due to that, it also relates the stress to the degeneration in the body tissues causing early aging and reduced life span. Although Acharya Caraka states that in order to stay healthy and to save the life one should always avoid over-exerting himself, however, in today’s world, stress is an inevitable part of life and so the stress induced diseases. Therefore, instead of looking for the stress avoidance strategy it is important to work on preventing the effects of stress on the body and increasing the coping capacity of the body by life style modifications, dietary interventions and other means. Ayurveda relate the Sahas to Vata aggravation in the body and provides the solution to the problem in the form of Vata balancing diet and activity regimen, Vasti therapy, rejuvenation or Rasayana therapy and application of Yoga and Pranayama.